2019
DOI: 10.1029/2019jg005265
|View full text |Cite
|
Sign up to set email alerts
|

Soil Respiration Variability and Correlation Across a Wide Range of Temporal Scales

Abstract: The high temporal variability of the soil-to-atmosphere CO 2 flux (soil respiration, R S ) has been studied at hourly to multiannual time scales but remains less well understood than R S spatial variability. How R S fluxes vary and are autocorrelated at various time lags has practical implications for sampling and more fundamentally for our understanding of its abiotic and biotic underlying mechanisms. We examined the variability, correlation, and sampling requirements of R S over a wide range of temporal scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…Jian et al (2018b) determined that this annual sampling frequency resulted in annual R S values that were within ±30% of the true R S mean 80% of the time. A similar conclusion was found in three temperate forests (Bond-Lamberty et al, 2019). This study thus demonstrated that while large uncertainty may exist with a 21-day measurement frequency, it may still reasonably capture the average annual mean of R S .…”
Section: 1029/2020jg006066supporting
confidence: 85%
See 1 more Smart Citation
“…Jian et al (2018b) determined that this annual sampling frequency resulted in annual R S values that were within ±30% of the true R S mean 80% of the time. A similar conclusion was found in three temperate forests (Bond-Lamberty et al, 2019). This study thus demonstrated that while large uncertainty may exist with a 21-day measurement frequency, it may still reasonably capture the average annual mean of R S .…”
Section: 1029/2020jg006066supporting
confidence: 85%
“…However, in a shrubland located at semiarid Mediterranean, California, measuring from 9:00 to 11:00 caused a bias of −29% to +40% compared with the diurnal mean R S flux (Cueva et al, 2017). The results from three mid-Atlantic deciduous forests showed that R S rate from mid-morning and late afternoon (15:00-16:00) were most close to the daily mean R S (Bond-Lamberty et al, 2019). At the global scale, Jian, et al (2018b) found that diurnal variation contributed less than 6% of bias to scale daily R S estimates; moreover, Jian, et al (2018b) showed that midmorning is a representative time window to capture diurnal mean R S because soil and air temperature reach diurnal mean between 9:00 to 12:00.…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 90%
“…While previous work has demonstrated the need for manipulative experiments with frequent sampling intervals (Vicca et al., 2014), the mechanism underlying this is not well understood. We strongly encourage new data syntheses explicitly focused on this phenomenon, and field experiments that prioritize measurements at shorter timescales (Bond‐Lamberty et al., 2019). Additionally, our results are sensitive to the limited amount of data from long‐term experiments, especially in desert ecosystems where only one study (Li et al., 2020) contributed data for more than 1 year.…”
Section: Discussionmentioning
confidence: 95%
“…In the interannual scale, previous studies showed that soil respiration variation is more substantially dominated by soil moisture or is rainfall-dependent [14,16,17]. Recent reports highlighted that the longterm interannual variability of soil respiration cannot be fully explained by climatic factors alone, but eco-physiological factors such as GPP, phenomenon, and fine root turnover should also be taken into account [18][19][20][21]. All this evidence indicated that the patterns of soil respiration may be dominated by different driving factors at different timescales.…”
Section: Introductionmentioning
confidence: 99%